Physiological Energy and Body Composition Reaction After 6 Weeks of Training at 2500m Hypoxia Chamber of Male Sprint - Ngoc, Luong Thi Anh; Duy, Nguyen Khanh; Tien, Nguyen Tien (Journal of Sports Research, 2019)
The study was to verify the influence of environment assumed elevation (FiO = 15.72% with the altitude 2500m) intermittently to change certain physiological functions, biochemical and body composition of male sprinters in this study. For 6 weeks, all subjects performed three high intensity interval training sessions per week. During the interval training sessions, the (H) group trained in a normobaric hypoxic chamber at a simulated altitude of 2500m, while the group (C) performed interval training sessions under normoxia conditions also inside the chamber. Each interval running training sessions consisted of four to five 5 min bouts at 90% of VO2max velocity determined in hypoxia (VO2max-hyp) for the (H) group and 90% of velocity at VO2max determined in normoxia for the group (C). (The speed was increased linearly by 1 km/h per 1min until volitional exhaustion in a run of ≥5 minutes). The results showed that both groups had significant changes (p <0.05), but the analysis showed that group (H) in the training in hypoxia caused changes significant (p <0.05), better than group (C) (HRmin reduce -9.17bpm, vital capacity (VC) to 0.42 liters, increase in 3000m run (0.94%), VO2max (3.98%), hemoglobin (1.3%), hematocrit (3:47 %), EPO decreased -2.07%).